Kenedi se zeni . Kenedi Is Getting Married - Žilnik, Želimir (Žilnik, Želimir, 2007)
Duration: 01:20:00 Kenedi is in huge debt after building a house for his family. He finds himself searching for any kind of work to support himself, for as little as 10 EUR per day, a scarce amount to help him relief his debt. Ultimately, Kenedi decides to look for money in sex business. Initially offering his services to older ladies and widows, he expands his ‘business’ to offer sex to wealthy men. When he finds out about new liberal European laws on gay marriages, Kenedi sees prospects in looking for a “marriage material”, to renew his search for a legal status in EU. The opportunity arises during EXIT Music Festival, when he meets Max, a guy from Munich. But will their promising relationship bring the solution to Kenedi’s problems?